A rare case of right trigeminal neuralgia due to dural arteriovenous fistula - Ghodasara, Sagar; Balasubramanian, Rohit; Poyyamoli, Santhosh (Asian Journal of Neurosurgery, 2021)
Trigeminal neuralgia (TGN) is often caused by a neurovascular conflict at the root entry zone of the fifth nerve. Dural arteriovenous fistula (DAVF) accounts for 3%–4% cases of TGN. We report a posttraumatic head injury patient, presenting with gait ataxia and right facial pain. Radiographic evidence with magnetic resonance imaging and digital subtraction angiography was suggestive of DAVF. Surgical clipping and obliteration of fistula alleviated the TGN.
Keywords: Arterialized dural petrosal vein; clipping and microvascular decompression; digital subtraction angiography; dural arteriovenous fistula; meningohypophyseal trunk; trigeminal neuralgia